Peanut hulls, an underutilized nutritious culinary ingredient: valorizing food waste for global food, health, and farm economies—a narrative review - Gerber, Suzannah; Roberts, Susan B. (Frontiers in Nutrition, 2024)
Peanut hulls (PHPHs) are an edible food waste that is an underutilized food source for human consumption. While edible and palatable, currently they are mainly diverted to livestock feed or building materials. Here, we describe existing literature onsupporting human food valorization of PHs, and propose methods to optimize recapturing nutrients (e.g. protein, fiber, polyphenolsphenols and other phytonutrients) lost by treating PHs as waste. Incorporated into common foods, PHs cancould be processed into functional ingredients to improve nutrient-density and thewith anticipated corresponding positive health outcomes associated with increases in plant foods. PH valorization can also address additionalValorization of PHs addresses multiple priorities of the UN Sustainable Development Goals using a Food Systems Approach (FSA) including reducing food waste, increasing economic opportunities for farmers, and increasing the availability of healthy shelf-stable foodstuffs to address food security. Recent advances in sustainable food processing technologies can be utilized to safely incorporate peanut hullsPHs into human food streams. We propose future applications that could make meaningful impacts tofor food availability and the nutritional composition of common foods like bread and plant-based meat alternatives. While the limited literature on this topic spans several decades, no commercial operations currently exist to process peanut hullsPHs for human consumption, and most literature on the topic precedes the technological 'green revolution'. The approaches outlined in this review may help bolster commercialization of this underutilized and nutritious food potentially improving opportunities for multiple global stakeholders.